Clinical and splenectomy-based treatment outcomes in 40 cases of hepatosplenic T-cell lymphoma: a comprehensive analysis - Mingyue-Chen; Min Wu; Yanhui-Xie; Lin Shen (World Journal of Surgical Oncology)
Abstract Background/aim This research study was conducted to examine the clinical characteristics and post-splenectomy survival outcomes of patients diagnosed with hepatosplenic T-cell lymphoma (HSTCL). Materials and methods A total of 10 cases of HSTCL patients admitted to the Hematology Department of Fudan University Affiliated Huadong Hospital between January 2012 and December 2021 were included. In addition, we also included 30 other cases reported from domestic and international sources. All pathological specimens were stained with hematoxylin and eosin (H&E) and immunohistochemistry, with color development using DAB staining. Survival analysis was conducted using Kaplan-Meier curves and log-rank tests. Results In the 10 HSTCL patients, Epstein-Barr virus (EBV) infection was confirmed. Six patients had died, with 5 of them within 1 year of disease onset. Survival analysis showed poorer prognosis in patients with hemophagocytic syndrome and thrombocytopenia. Patients who underwent splenectomy followed by chemotherapy had a higher median and average survival time compared to those who only received chemotherapy. The study included a total of 40 HSTCL patients, with 29 males and 11 females, and an average age of onset at 42.3 years. All patients presented with fever, with some exhibiting emaciation and/or hemophagocytic syndrome. Splenomegaly, hepatomegaly, lymphadenopathy, and bone marrow involvement were found in the patients. Common laboratory findings included leukopenia, anemia, and thrombocytopenia. All patients exhibited elevated ferritin levels and decreased blood calcium levels. Conclusion Those patients suffering from hemophagocytic syndrome at the onset of this disease face greater treatment-related difficulties and a higher risk of mortality. Combined chemotherapy after splenectomy may improve HSTCL patient survival.